2:30 - A Stop-Motion Short Film - Sophie Caswell (UNC Test Journal, 2025)
2:30 (2025) is a five-minute stop-motion animated short film set in an anachronistic world, exploring addiction, obsession, and the myth of the tortured artist. In a dark and cramped attic, Luna, a moth with dreams of being a dentist, sets up her first professional practice at home. As she works, she discovers an intoxicating euphoria in the glow of her dental light, forming an obsession that fuels her craft and enhances her skills. As the days blur together, her fixation deepens and her artistry decays along with her sanity. This film is a haunting, tactile exploration of artistic obsession, existing within the horror and sci-fi genres. Through meticulously crafted puppets and sets, the theme of addiction within the art community and the breakdown of the myth of the tortured artist trope are both explored, uniquely drawing connections with the symbolism and beauty of nocturnal insects. Addiction and mental illness are investigated alongside research involving the craft of stop-motion animation. Through the pre-production process, sustainable fabrication, frame-by-frame animation, and post-production, this dark tale is told through a display of traditional animation, one infused with the essence of human touch, personal experience, and creative exploration.